INTEGRASI SAINS DAN AGAMA DALAM PEMBELAJARAN KURIKULUM PAI (Perspektif Islam dan Barat serta Implementasinya) - Rabiatul Adawiyah (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
The Islamic teachings contain various moral and ethical values which is very important in today's modern era because Islam always concerns with the balance between body and spirit, inward and outward, spiritual and the material, between world and hereafter. Islam can provide moral and ethical values in the development of science. With religion, it is expected that man does not forget himself after successfully developing science, and aware that the science he developed is an ongoing effort within the framework of worship. Therefore, through science, humans will find the ultimate truth that is God. Science is one of the strategic doors to bring people closer to God through intensive and serious effort to consider the universe to the perfection of human life, both physically and spiritually. Through the integration of science and religion developed in PAI (Islamic Education), it is expected to produce the learners who have a scientific attitude, scientific responsibility, capability of utilizing science and become ululalbab.